DEVELOPING INSTRUCTIONAL MATERIALS ON ENGLISH ORAL COMMUNICATION FOR NURSING SCHOOLS - Sismiati Sismiati; Mohammad Adnan Latief (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
The needs survey shows that English communication skill of the students in nursing school speaking classes is not well developed. Consequently, the speaking instructional materials used in the classes need to be advanced. Yaldenâs (1987) Language Program Development covering Needs Analysis, Syllabus and Materials Development, Expert Validation, and Try-out is used to produce a speaking syllabus and textbook for nursing students preparing to work at hospitals abroad with the following characteristics: (1) the topics are based on the activities of nurses in hospitals; (2) the vocabulary exercises are based on the nursesâ needs in under- standing the nursing context; (3) the speaking activities are based on the needs to communicate in nursing settings using the principles of CTL; (4) the language functions are explained to support the nursing students to form their own sentences in their speaking practice. The product is found acceptable for nursing students.